Cooperative Game Theory Tools in Coalitional Control Networks - Muros, Francisco Javier; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book analyzes coalitional control schemes by incorporating concepts of cooperative game theory into a distributed control framework. It considers a networked architecture where the nodes are the agents and the edges are their communication links and either the agents or the links are established as the players of cooperative games related to the cost function of the coalitional schemes. The book discusses various cooperative game theory tools that are used to measure/analyze the players' features, impose constraints on them, provide alternative methods of game computation, detect critical players inside the control scheme, and perform system partitioning of large-scale systems, such as the Barcelona drinking water network, which is described in a case study.
Introduction -- Cooperative Game Theory -- Coalitional Systems in Optimal Control -- The Shapley and Position Values to Design Coalitional Networks -- The Banzhaf Value as a Design Tool in Coalitional Control -- Harsanyi Power Solutions in Coalitional Control Systems -- Detection of Critical Agents by the Position Value -- Partitioning of Coalitional Networks by Cooperative Game Theory -- Conclusions and Future Research.
Keywords: Control engineering; Game theory; Computational intelligence; Control and Systems Theory; Game Theory; Computational Intelligence